Implikasi Hukum Bisnis Atas Pelanggaran Hak Cipta Penggunaan Foto Produk Tanpa Izin di Marketplace Digital - Sesilia Faustin Alisa Purwantoro; Chintya Inayah; Sri Handayani (Equivalent : Journal of Economic, Accounting and Management, 2025)
Abstract : Product photography serves as the first visual impression and holds significant importance. This study examines the legal protection, causes, and resolution efforts regarding the unauthorized use of product photography on online shopping platforms. Using a qualitative approach through literature study (library research), the findings show that protection can be implemented through preventive measures such as copyright registration and repressive measures, including both litigation and non-litigation mechanisms. Applicable sanctions include civil compensation (Articles 95–99 of the Copyright Law), imprisonment and/or fines (Article 113 of the Copyright Law), as well as administrative penalties in accordance with Government Regulation Number 80 of 2019 concerning Trade through Electronic Systems, such as business license revocation and cessation of business operations. The increasing cases of product photo theft are driven by low copyright awareness, the absence of a dedicated Collective Management Organization for photography, and limited public outreach. It is recommended that the government enhance copyright education, strengthen inter-agency coordination, and encourage proactive efforts from business actors as an integrated approach to effectively ensure the protection of product photography works. Abstrak : Foto produk merupakan kesan pertama yang dilihat dan menjadi sangat penting. Penelitian ini mengkaji perlindungan hukum, penyebab, dan upaya penyelesaian atas penggunaan fotografi produk pada platform online shop tanpa izin. Melalui metode pendekatan kualitatif dengan metode studi literature (library research), ditemukan bahwa perlindungan dapat melalui tindakan preventif seperti pendaftaran hak cipta dan perlindungan represif meliputi mekanisme litigasi dan non litigasi. Sanksi yang diterapkan meliputi ganti rugi atas dasar hukum perdata (Pasal 95–99 UUHC), pidana penjara dan/atau denda (Pasal 113 UUHC), serta sanksi administratif sesuai Peraturan Pemerintah Nomor 80 Tahun 2019 tentang Perdagangan Melalui Sistem Elektronik seperti dilakukan pencabutan izin usaha dan penghentian kegiatan usaha. Maraknya pencurian foto produk dikarenakan rendahnya kesadaran hak cipta, belum adanya Lembaga Manajemen Kolektif khusus fotografi, dan minimnya sosialisasi. Disarankan peningkatan edukasi hak cipta oleh pemerintah, penguatan koordinasi antar-instansi, serta langkah proaktif pelaku usaha sebagai upaya terpadu menjamin perlindungan karya fotografi produk secara efektif.